2009
DOI: 10.1080/00207450802507689
|View full text |Cite
|
Sign up to set email alerts
|

Red Light Facilitates the Sensed Presence Elicited by Application of Weak, Burst-Firing Magnetic Fields Over the Temporal Lobes

Abstract: To test the hypothesis that the wavelength (color) of ambient lightning should modulate experiences of a sensed presence when the right hemisphere was stimulated by weak, burst-firing magnetic fields, volunteers were exposed for 30 min to this condition or to a sham field while they sat (eyes opened) in either dim red, green, or white light. Subjects exposed to the magnetic field reported significantly more visual sensations along the left side in red light and along the right side in green light. The signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Our lab has previously shown that exposures to specific time-varying, physiologically patterned, propagating electromagnetic fields (EMF) can affect biological systems [22][23][24][25][26][27][28][29][30]. For example, exposure to a frequency-modulated EMF called the Thomas-EMF is capable of reducing proliferation of B16-BL6 melanoma cells in vivo and in vitro [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has previously shown that exposures to specific time-varying, physiologically patterned, propagating electromagnetic fields (EMF) can affect biological systems [22][23][24][25][26][27][28][29][30]. For example, exposure to a frequency-modulated EMF called the Thomas-EMF is capable of reducing proliferation of B16-BL6 melanoma cells in vivo and in vitro [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Persinger and colleagues' experimental research on magnetic field exposure has often been conducted using a device of their own design (often referred to as the "Koren" helmet), which consists of eight magneticfield producing solenoids attached to a motorcycle helmet (Persinger, et al, 1994Freeman & Persinger, 1996;Meli & Persinger, 2009). Research using the Koren helmet and similar devices has shown that exposure to purposefully constructed weak and complex magnetic fields (in contrast to exposure to sham magnetic fields) results in increased sensedpresence experiences and other perceptual and neurophysiological alterations (Persinger, et al, 1994Roll, et al, 2002;Hill & Persinger, 2003;Booth, et al, 2005;Meli & Persinger, 2009).…”
mentioning
confidence: 99%
“…In particular, the work of Michael Persinger has received substantial attention. In addition to research examining the effects of naturally fluctuating geomagnetic activity (Booth, Koren, & Persinger, 2005), Persinger and colleagues have published a number of studies using controlled experimental procedures to assess the psychological effects of exposure to weak and complex magnetic fields (Persinger, Richards, & Koren, 1994;Baker-Price & Persinger, 1996Freeman & Persinger, 1996;Persinger, Tiller, & Koren, 2000;Roll, Persinger, Webster, Tiller, & Cook, 2002;Tsang, Koren, & Persinger, 2004;Booth, et al, 2005;Meli & Persinger, 2009). Persinger and colleagues' experimental research on magnetic field exposure has often been conducted using a device of their own design (often referred to as the "Koren" helmet), which consists of eight magneticfield producing solenoids attached to a motorcycle helmet (Persinger, et al, 1994Freeman & Persinger, 1996;Meli & Persinger, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations